The Bible in Motion: a Handbook of the Bible and Its Reception in Film - Burnette-Bletsch, Rhonda (Handbooks of the Bible and its reception, 2016)
This two-part volume contains a comprehensive collection of essays by well-known scholars focusing on the reception of the Bible in world cinema. It explores selected biblical characters and themes, directors whose work addresses biblical texts and motifs, particular interpretive lenses, a wide array of film genres, and a variety of world cinemas. It is intended for scholars of the Bible, religion, and film as well as for a general audience.